Pengaruh Persepsi Good Leadership, Persepsi Kualitas Interaksi Atasan-Bawahan dan Dukungan Sosial Terhadap Organizational Citizenship Behavior - Rizky Sandhi Setyaki; Franciscus Xaverius Nicolas Susanto; David Adechandra Ashedica Pesudo (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
This research was conducted to investigate the relationshipbetween Perceived of Good Leadership, Perceived Leader-MemberInteraction Quality and Social Support on Employee’s OrganizationalCitizenship Behavior. The Subjects of this study were SME employees witha total response of 64 out a total of 70 questionnaires in Salatiga City. The samples of this study were taken using the Purposive-Judgement methodwith Quota Sampling. It was found which there was a significant positiverelationship between perceived Perceived Leader-Member InteractionQuality and Social Support on Employee’s Organizational CitizenshipBehavior with a significance level of 0,001 and 0,000 for each variable.While the significance level of 0,928 in the variable of Perceived of GoodLeadership shows no influence on Employee’s Organizational CitizenshipBehavior. The influence of independent variables on the dependent variablein the F test is also indicated by the number of 8.794, where it concludesthat the independent variables simultaneously influence the dependentvariable. In addition, the coefficient of determination level shows thatindependent variables contribute 45,7% to the independent variable, whilethe remaining 54,3% is explained by other variables.